Indefeasibility of title under The Torrens System and The Malaysian National Land Code 1965 / Rosni Zahari - Zahari, Rosni (Faculty of Law, 1986)
The Torrens System of registration of land titles, with ideals of the liability, simplicity, speed and low cost, originated in the State of South of Australia in 1857 and become law there in 1891 by Sir William Maxwell and enacted as law for Singapore on 12th June 1956 with the passing of the Land Titles Ordinance. Beside the other states of Australia some of the countries where it is in operation are New Zealand, Canada, United States of America, Nigeria, Northern Ireland, Brunei and Fiji Island. Gradual transfer to this system is the aim in England and Wales where it is at, present compulsory in certain areas and optional in others. The Torrens System is a system are cord where the recognition of this record was done under the statutory provision. The provisions provides that the register is everything. It is where the titles to land rest and titles shall pass when a designated official of the State Register of Transfer which is made out and presented to the official on prescribed form. It is the state who can effectively transfer the land, not the parties.